School Based Management Committee and Quality Education in basic Schools in Ilorin Metropolis, Kwara State - Yusuf , Adedayo Abdulkareem; Mustapha, Adam Ishola; Yusuf , Suleiman (International Journal of Educational Management, 2022)
The study investigated school based management committee and quality education in basic schools in Ilorin metropolis. The researcher employed descriptive survey of correlational type for the study. Random sampling technique was used to select 10 public basic schools and 100 participants from the five Local Government Areas that constitute Ilorin Metropolis. The researcher designed Questionnaire titled “School Based Management Committee and Quality Education Questionnaire (SBMCQEQ)” were used to elicit relevant data from the sampled respondents. Two research hypotheses were formulated and tested using Pearson product moment correlation statistics. The results of the findings revealed that significant relationships exist between School based management committee and quality education in Ilorin metropolis basic schools. Recommendations were made in the light of the findings that effort should be made by parents to help teachers at home in playing the role of a semi-teacher through effective monitoring of the progress of their wards. Also, every member of the community should give education top most priority and be fully involved towards ensuring quality education in basic schools.